Binder as well as preparation method and application thereof
By using polymer binder containing conductive segments in lithium batteries, the problem of bond failure caused by volume changes in silicon-carbon composite materials during charging and discharging is solved, and the dynamic performance and cycle stability of the battery are improved.
Patent Information
- Application Number
- CN202411811061.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The volume expansion and contraction of silicon-carbon composite materials in lithium batteries leads to bond failure during charging and discharging, affecting the cycle life of the battery and the stability of the electrical performance. At the same time, the poor dispersion of the conductive agent leads to low electrical conductivity.
A polymer binder containing conductive segments is used, which forms a crosslinked structure through free radical polymerization, is versatile, and forms a stable conductive binder network through conductive polymer copolymerization.
The binder can directly conduct electrons, reduce the electrode sheet resistance, increase the content ratio of active substances, enhance the energy density of the electrode sheet and the overall performance of the battery, and effectively disperse and stabilize the silicon and carbon materials to prevent agglomeration and settlement.
Smart Images

Figure CN119890311A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery materials, and in particular to a binder and a preparation method and application thereof. Background Art
[0002] Among the negative electrode materials of lithium batteries, silicon-carbon composite materials have attracted much attention due to their high capacity advantage. However, silicon-carbon particles will undergo significant volume expansion and contraction during the charge and discharge process, resulting in failure of the bonding between particles and current collectors, and between particles, thereby causing problems such as increased battery thickness and increased internal resistance, which seriously affects the cycle life and electrical performance stability of the battery. On the other hand, pure silicon materials have low conductivity and need to be enhanced by adding conductive agents such as SP. However, the poor dispersibility of these conductive agents may lead to a decrease in the proportion of active materials, further affecting the energy density and low-temperature performance of the battery.
[0003] Therefore, it is urgent to find an adhesive to solve the problems of adhesive failure, low conductivity and the like existing in the above-mentioned prior art. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a binder that effectively solves the problem of bonding failure and improves the dynamic performance and electrical performance of the battery.
[0005] The invention also provides a method for preparing the binder.
[0006] The present invention also provides a negative electrode sheet comprising the binder.
[0007] The present invention also provides a battery comprising the negative electrode plate.
[0008] According to an embodiment of the first aspect of the present invention, there is provided a bonding agent, wherein the pole piece comprises:
[0009] The binder is a polymer containing the following structural units:
[0010] The binder comprises a structural unit shown in general formula I:
[0011]
[0012] Wherein, M is at least one of H, Na, Li, and K;
[0013] R1 and R2 each independently include at least one of H, substituted or unsubstituted C1-10 straight or branched alkyl; R3 is a conductive polymer; R4 and R5 each independently include at least one of H, C1-10 straight or branched alkyl, and C1-10 alkanoyloxy;
[0014] n1 is an integer from 10 to 100, n2 is an integer from 2 to 20, and n3 is an integer from 10 to 35;
[0015] m1 is an integer from 10 to 50; m3 is an integer from 2 to 30; m4 is an integer from 10 to 100, m5 is an integer from 10 to 100; m7 is an integer from 5 to 20; wherein, m2+m6 is an integer from 300 to 3000.
[0016] The adhesive according to the embodiment of the present invention has at least the following beneficial effects:
[0017] The binder of the present invention contains conductive segments that can directly conduct electrons, thereby reducing the resistance of the electrode. Compared with the traditional method, there is no need to add additional conductive agents such as SP and CNT in the silicon system, which not only simplifies the material formula, but also increases the content ratio of active substances, thereby improving the energy density of the electrode and the overall performance of the battery.
[0018] The binder of the present invention can directly coat the surface of the active material, efficiently disperse and stabilize particles of silicon materials, carbon materials, etc., and prevent their agglomeration and sedimentation. Compared with the traditional CMC dispersant, due to the incomplete coating of the chain structure, the contact area between the active material and the electrolyte can be effectively increased, thereby improving the dynamic performance and cycle stability of the battery.
[0019] According to some embodiments of the present invention, the main chain polymer monomer includes polyacrylic acid monomer, polyacrylate monomer, and linear or branched alkyl polymer monomer having 1 to 4 carbon atoms.
[0020] According to some embodiments of the present invention, m2 and m6 are the polymerization degrees of polyacrylic acid monomers.
[0021] According to some embodiments of the present invention, m4 is the degree of polymerization of the polyacrylate monomer.
[0022] According to some embodiments of the present invention, m1 is the number of branches of the polyacrylic acid monomer.
[0023] According to some embodiments of the present invention, m3 is the number of branches of the polyacrylamide monomer.
[0024] According to some embodiments of the present invention, m5 is the number of branches of a linear or branched alkyl polymer monomer having 1 to 4 carbon atoms.
[0025] According to some embodiments of the present invention, m7 is the number of branches of the conductive polymer.
[0026] According to some embodiments of the present invention, the conductive polymer comprises thiophenes or aniline.
[0027] According to some embodiments of the present invention, the solid content of the binder is 1%-15%.
[0028] Preferably, the solid content of the binder is 5%-10%.
[0029] According to some embodiments of the present invention, the viscosity of the adhesive is 1000-100000 mPa·s.
[0030] Preferably, the viscosity of the adhesive is 8000-25000 mPa·s.
[0031] According to an embodiment of the second aspect of the present invention, a method for preparing the binder is provided, the steps of the preparation method comprising:
[0032] S1, mixing acrylic acid, a first initiator and a solvent under an inert atmosphere to carry out a first reaction to obtain a first product, and then continuing to react a crosslinking agent, polyacrylamide, paraffin and acrylate, adjusting the pH, and drying to obtain a second product;
[0033] S2, dissolving the second product, adding a conductive polymer, a cross-linking agent, and a second initiator to carry out a second reaction, and filtering to obtain the binder.
[0034] The structural formula of the first product, Formula I, and the structural formula of the second product, Formula II, are as follows:
[0035]
[0036] The preparation method according to the embodiment of the present invention has at least the following beneficial effects:
[0037] The preparation method of the present invention generates polyacrylic acid through free radical polymerization, and the double bonds of acrylic acid are opened under the action of free radicals to form active centers that continuously polymerize to form long-chain polymers. During the polymerization reaction, the double bonds of the crosslinking agent react with the active centers on the polyacrylic acid chain to form a crosslinking structure, thereby improving the mechanical strength and stability of the polymer. In the continued polymerization reaction, monomers such as polyacrylamide, paraffin and acrylate copolymerize with the polyacrylic acid chain to form a polymer with multiple functional groups, thereby improving the multifunctionality of the binder. The conductive polymer and the second product undergo a copolymerization reaction, so that the binder has conductivity, and a more stable binder network structure is formed, thereby ensuring the physical and chemical stability of the binder during use.
[0038] The adhesive provided by the present invention is designed as a solution and can be directly added to a stirring tank for slurry preparation. Unlike traditional CMC gluing, there is no need to prepare glue solution in advance, which saves equipment for gluing, improves production efficiency and reduces manufacturing costs.
[0039] According to some embodiments of the present invention, in step S1, the first initiator is azobisisobutyronitrile (AIBN, CAS No.: 78-67-1).
[0040] According to some embodiments of the present invention, in steps S1 and S2, the cross-linking agent is N,N'-methylenebisacrylamide (MBAA, CAS No.: 110-26-9).
[0041] According to some embodiments of the present invention, in step S2, the conductive polymer includes thiophenes or aniline (ANI, CAS No.: 62-53-3).
[0042] Preferably, in step S2, the thiophenes include 3,4-ethylenedioxythiophene (EDOT).
[0043] According to some embodiments of the present invention, in step S2, the second initiator includes ammonium persulfate (APS, CAS No.: 7727-54-0).
[0044] According to some embodiments of the present invention, in step S1, relative to 500 parts by weight of acrylic acid, the amount of the prepared raw materials includes: 1 to 3 parts by weight of a first initiator, 0.1 to 0.3 parts by weight of a cross-linking agent, 2 to 7 parts by weight of polyacrylamide, 20 to 60 parts by weight of paraffin, and 100 to 200 parts by weight of acrylate.
[0045] Preferably, in step S1, relative to 500 parts by weight of acrylic acid, the amount of the prepared raw materials includes: 2 parts by weight of a first initiator, 0.2 parts by weight of a cross-linking agent, 15 parts by weight of polyacrylamide, 50 parts by weight of paraffin, and 170 parts by weight of acrylate.
[0046] According to some embodiments of the present invention, in step S2, relative to 400 parts by weight of the second product, the amount of the preparation raw materials includes: 60 to 100 parts by weight of a conductive polymer, 0.3 to 0.5 parts by weight of a second initiator, and 0.5 to 0.7 parts by weight of a cross-linking agent.
[0047] Preferably, in step S2, relative to 400 parts by weight of the second product, the amount of the preparation raw materials includes: 80 parts by weight of the conductive polymer, 0.4 parts by weight of the second initiator, and 0.6 parts by weight of the cross-linking agent.
[0048] According to some embodiments of the present invention, in step S1, the solvent is methanol.
[0049] According to some embodiments of the present invention, in step S1, the reaction temperature is 50-70°C, for example, 50°C, 55°C, 60°C, 65°C, or 70°C.
[0050] According to some embodiments of the present invention, in step S1, the time of the first reaction is 20 to 40 min, for example, 20 min, 25 min, 30 min, 35 min, or 40 min.
[0051] According to some embodiments of the present invention, in step S1, the time of the second reaction is 3 to 4 hours, for example, 3 hours, 3.5 hours, or 4 hours.
[0052] According to some embodiments of the present invention, in step S1, the pH adjustment step includes using sodium hydroxide to adjust the pH value to 6-6.5.
[0053] According to some embodiments of the present invention, in step S1, the inert atmosphere includes at least one of nitrogen, argon, and helium.
[0054] According to some embodiments of the present invention, in step S1, the paraffin wax is a mixture of alkanes having 14 to 30 carbon atoms and a melting point of 5.5 to 65.5°C;
[0055] Preferably, in step S1, the paraffin wax is a mixture of alkanes with 14 to 22 carbon atoms and a melting point of 5.5 to 44.4°C.
[0056] According to some embodiments of the present invention, in step S2, the solvent for dissolving the second product is a mixed solvent of dimethyl sulfoxide and water.
[0057] According to some embodiments of the present invention, the ratio of dimethyl sulfoxide to water is 1:5 to 1:10.
[0058] According to some embodiments of the present invention, in step S2, the reaction temperature is 60-70°C, for example, 60°C, 62°C, 65°C, 68°C, or 70°C.
[0059] According to some embodiments of the present invention, in step S2, the reaction time is 1 to 3 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours, or 3 hours.
[0060] According to an embodiment of the third aspect of the present invention, there is provided a negative electrode sheet, comprising a negative electrode active material and the above-mentioned binder;
[0061] According to some embodiments of the present invention, the negative electrode active material includes a carbon material and / or a silicon material.
[0062] According to some embodiments of the present invention, the mass ratio of the carbon material, the silicon material and the binder is (91-93): (4-6): (2-4).
[0063] According to some embodiments of the present invention, the mass ratio of the carbon material, the silicon material and the binder is 92:5:3.
[0064] According to an embodiment of the third aspect of the present invention, there is provided a lithium battery, comprising the above-mentioned negative electrode plate, as well as a positive electrode plate, a separator and an electrolyte.
[0065] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.
[0066] Unless otherwise specified, “between” in the present invention includes the number itself, for example, “between 2 and 3” includes the endpoint values 2 and 3.
[0067] The structural formulas in the present invention appear Indicates the junction position between the main chain polymer and the branched polymer.
[0068] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. DETAILED DESCRIPTION
[0069] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0070] In the description of the present invention, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention based on the specific content of the technical solution.
[0071] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0072] Example 1
[0073] This embodiment provides a binder, and the specific preparation method thereof includes:
[0074] Step 1: Add 500 parts of acrylic acid, 90 parts of butyl acrylate, 2 parts of AIBN as an initiator, and an appropriate amount of methanol as a solvent, introduce N2, react at 60°C for 30 minutes, keep warm at 45°C for 20 minutes, and dry to remove the solvent to obtain the first product;
[0075] The first product has the following structural formula:
[0076]
[0077] Step 2: 600 parts of the first product, 5 parts of AIBN initiator, 0.2 parts of cross-linking agent N,N'-methylenebisacrylamide (MBAA), toluene as solvent, 60°C for 30 minutes, 70 parts of acrylic acid, 15 parts of acrylamide, 50 parts of molten paraffin were added dropwise, N2 was introduced, 60°C for 3 hours, NaOH was added to adjust the pH to 6.5, the solvent was removed and dried to obtain the second product;
[0078] The second product structural formula is as follows:
[0079]
[0080] Step 3: 80 parts of 3,4-ethylenedioxythiophene (EDOT) were dissolved in a mixed solvent of dimethyl sulfoxide and water, 0.4 parts of initiator ammonium persulfate (APS), 0.6 parts of cross-linking agent N,N'-methylenebisacrylamide (MBAA), and 400 parts of the second product were added, and the mixture was reacted at 45°C with stirring for 10 hours, and the dimethyl sulfoxide was removed by reduced pressure distillation at 60°C, and the pH was adjusted to 7 to obtain the final product binder, the structural formula of which is as follows:
[0081]
[0082] This embodiment also provides a negative electrode sheet, and the specific preparation method includes:
[0083] Graphite, silicon and the above-mentioned binder are mixed in a mass ratio of 92:5:3, and the negative electrode slurry is obtained after sufficient stirring and dispersion. The negative electrode sheet is prepared through the processes of baking, rolling, striping, and welding the pole ears.
[0084] This embodiment also provides a lithium ion battery, and the specific preparation method includes:
[0085] Preparation of positive electrode sheet: active material lithium cobalt oxide, conductive carbon black, and binder PVDF (CAS No.: 24937-79-9) are mixed in a mass ratio of 96:2:2, and N-methylpyrrolidone (NMP, CAS No.: 872-50-4) is added and stirred thoroughly to obtain positive electrode slurry, which is evenly coated on the positive electrode current collector aluminum foil, and prepared into positive electrode sheet through baking, rolling, striping, welding of pole ears and other processes.
[0086] Preparation of lithium-ion battery: Assemble the above-mentioned positive electrode sheet, the above-mentioned negative electrode sheet, the separator, and the aluminum-plastic film, inject the electrolyte after baking, and go through the processes of standing, forming, secondary sealing, and testing to obtain a lithium-ion battery.
[0087] Example 2
[0088] Compared with Example 1, this embodiment is different in that the preparation method of the binder is different, specifically including:
[0089] Step 3: Add 2.2 parts of initiator APS ammonium persulfate, 8000 parts of water, 400 parts of the second product, 34 parts of dodecylbenzenesulfonic acid (DBSA), pass N2 protection, drop 80 parts of aniline (ANI), react at 55°C with stirring for 13 hours, use ammonia water to adjust the pH to 7, and obtain the binder, the structural formula of which is as follows. The rest is the same as Example 1.
[0090]
[0091] Wherein, X: the reduction unit of polyaniline; 1-X: the oxidation unit of polyaniline; n4: the degree of polymerization of the polyaniline side chain.
[0092] Embodiments 3 to 9
[0093] The parts of each monomer are shown in Table 1, and the rest are the same as in Example 1.
[0094] Table 1 Monomer parts of Examples 1 to 9 of the present invention
[0095]
[0096]
[0097] Table 2 Corresponding values of n1-n4, m1-m7 in Examples 1-9 of the present invention
[0098] <![CDATA[n1]]> <![CDATA[n2]]> <![CDATA[n3]]> <![CDATA[n4]]> <![CDATA[m1]]> <![CDATA[m2+m6]]> <![CDATA[m3]]> <![CDATA[m4]]> <![CDATA[m5]]> <![CDATA[m7]]> Example 1 15 4 18 10 20 600 5 70 25 12 Example 2 15 4 18 16 20 600 5 70 25 12 Example 3 15 4 18 8 20 600 5 49 25 12 Example 4 20 4 18 10 20 600 5 70 25 12 Example 5 15 10 18 10 20 600 5 70 25 12 Example 6 15 4 18 10 20 600 5 70 33 12 Example 7 15 4 18 10 20 600 5 78 25 12 Example 8 15 4 18 8 20 600 5 70 25 12 Example 9 15 4 18 5 20 600 5 70 25 12
[0099] Comparative Example 1
[0100] This comparative example provides a pole piece, which is different from Example 1 in that it includes graphite, silicon, dispersant CMC, and commercially available binder PAA in a mass ratio of 92:5:1:2.
[0101] This comparative example also provides a lithium ion battery, and the specific preparation method is the same as that of Example 1.
[0102] The CMC (sodium carboxymethyl cellulose) provided in this comparative example is CMC2200 produced by Daicel Corporation; and the PAA (polyacrylic acid) is LA133 produced by Indel Corporation.
[0103] Comparative Example 2
[0104] This comparative example provides a pole piece, which is different from Example 1 in that it includes graphite, silicon, dispersant CMC, commercially available binder PAA, and conductive agent CNT in a mass ratio of 91.5:5:1:2:0.5.
[0105] Test Example 1
[0106] The viscosity of the negative electrode slurries prepared in the above-mentioned Examples 1 to 9 and Comparative Examples 1 to 2 was tested, and the electrode resistance and electrode adhesion were tested. The results are shown in Table 2:
[0107] Viscosity: Mix the above raw materials directly in a stirring tank and stir evenly to form the above slurry. Stir for 60 minutes at a speed of 700 rpm. After standing for 24 hours, stir slowly at 200 rpm for 30 minutes and then test the viscosity.
[0108] Solid content: Take a slurry sample and place it in an oven at 150°C to dry to constant weight for 2 hours. Weigh the mass of the dried sample and calculate the solid content. The formula is as follows:
[0109]
[0110] Table 2 Test results of Examples 1 to 9 and Comparative Examples 1 to 2
[0111]
[0112] According to the results in Table 2, the viscosity of the slurries prepared in Examples 1 to 9 increased slightly after standing for 24 hours, and the solid content of the lower layer remained basically unchanged, indicating that no sedimentation occurred. The viscosity of the slurries prepared in Comparative Examples 1 to 2 increased significantly after standing, and obvious stratification and sedimentation occurred. At the same time, since the binder provided in Examples 1 to 9 dispersed the silicon-carbon-graphite mixed particles well, the electrode bonding force was significantly higher than that of Comparative Examples 1 to 2. From the electrode resistance data, it can be seen that at the same addition amount, the conductivity of Example 2 (aniline monomer) is slightly worse than that of Example 1 (3,4-ethylenedioxythiophene monomer), and increases with the decrease in the amount of monomer addition (Examples 8 and 9). In addition, the conductive groups of polythiophene and polyaniline conduct electrons, and the resistance of the electrode is significantly lower than that of Comparative Example 1.
[0113] Test Example 2
[0114] The batteries prepared in the above-mentioned Examples 1 to 9 and Comparative Examples 1 to 2 were subjected to low temperature discharge tests. The results are shown in Table 3:
[0115] The assembled battery capacity is 4600mAh. It is charged to 4.45V at 0.2C current at room temperature. It is left to stand for 1 hour to ensure that the battery is fully charged. The charged battery is placed in a 25℃ environment and discharged at 0.2C current. The discharge termination voltage is 3V. The discharge capacity at 25℃ is recorded as the reference capacity. The battery is placed in 0℃, -10℃, and -20℃ environments for 12 hours to allow the battery to reach a low temperature stable state.
[0116] Table 3 Battery capacity retention rate of Examples 1 to 9 and Comparative Examples 1 to 2
[0117]
[0118]
[0119] According to the data in Table 3, the low temperature performance of the batteries prepared in Examples 1 to 9 is significantly better than that of Comparative Examples 1 to 2, because the binder provided by the present invention can be dispersed and coated on the surface of active materials such as graphite and silicon carbon, and contains groups such as acrylic acid esters that are affinity for electrolytes, which enhances the lithium ion exchange rate between the active material and the electrolyte, and improves the charge and discharge efficiency and stability of the battery. At the same time, different acrylic acid ester monomers have different low temperature performances, and Example 1 (butyl acrylate) is better than Example 3 (isooctyl acrylate).
[0120] The present invention achieves efficient production, excellent active material dispersibility, improved battery performance, stable pole piece performance and superior low temperature performance through unique binder structure design and optimized preparation process.
[0121] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A binder, characterized in that: The binder comprises a structural unit of formula I: Wherein, M is at least one of H, Na, Li, and K; R1 and R2 each independently include at least one of H, substituted or unsubstituted C1-10 straight or branched alkyl; R3 is a conductive polymer; R4 and R5 each independently include at least one of H, C1-10 straight or branched alkyl, and C1-10 alkanoyloxy; n1 is an integer from 10 to 100, n2 is an integer from 2 to 20, and n3 is an integer from 10 to 35; m1 is an integer from 10 to 50; m3 is an integer from 2 to 30; m4 is an integer from 10 to 100, m5 is an integer from 10 to 100; m7 is an integer from 5 to 20; wherein, m2+m6 is an integer from 300 to 3000.
2. The adhesive according to claim 1, characterized in that The m1 is the number of branches of the polyacrylic acid monomer; and / or, the m3 is the number of branches of the polyacrylamide monomer; and / or, the m5 is the number of branches of a linear or branched alkyl polymer monomer having 1 to 4 carbon atoms; and / or, the m7 is the number of branches of the conductive polymer; and / or, the conductive polymer comprises thiophenes or aniline.
3. The adhesive according to claim 1, characterized in that The m2 and m6 are the polymerization degrees of the polyacrylic acid monomer; and / or, the m4 is the polymerization degree of the polyacrylate monomer.
4. The adhesive according to claim 1, characterized in that The solid content of the binder is 1%-15%; preferably, the viscosity of the binder is 1000-100000 mPa·s.
5. A method for preparing the adhesive according to any one of claims 1 to 4, characterized in that: The steps of the preparation method include: S1, mixing acrylic acid, a first initiator and a solvent under an inert atmosphere to carry out a first reaction to obtain a first product, and then carrying out a second reaction with a crosslinking agent, polyacrylamide, paraffin and acrylate, adjusting the pH, and drying to obtain a second product; S2, dissolving the second product, adding a conductive polymer, a crosslinking agent, and a second initiator to carry out a third reaction, and filtering to obtain the binder; The structural formula of the first product, Formula I, and the structural formula of the second product, Formula II, are as follows:
6. The preparation method according to claim 5, characterized in that: Also includes at least one of the following (1) to (8): (1) In step S1, the first initiator is azobisisobutyronitrile; (2) In steps S1 and S2, the cross-linking agent is N,N'-methylenebisacrylamide; (3) In step S2, the conductive polymer includes at least one of ethylenedioxythiophene and aniline; (4) In step S2, the second initiator includes ammonium persulfate; (5) the pH value in step S1 is 6 to 7; (6) The reaction temperature in step S1 is 50 to 70° C.; (7) The reaction temperature in step S2 is 60-70° C.; (8) In step S1, the paraffin wax is a mixture of alkanes with 14 to 30 carbon atoms and a melting point of 5.5 to 65.5°C; and / or, in step S1, the paraffin wax has 14 to 22 carbon atoms and a melting point of 5.5 to 44.4°C.
7. The preparation method according to claim 5, characterized in that: In step S1, relative to 500 parts by weight of acrylic acid, the amount of the prepared raw materials includes: 1 to 3 parts by weight of a first initiator, 0.1 to 0.3 parts by weight of a cross-linking agent, 2 to 7 parts by weight of polyacrylamide, 20 to 60 parts by weight of paraffin, and 100 to 200 parts by weight of acrylate.
8. The preparation method according to claim 5, characterized in that: In step S2, relative to 400 parts by weight of the second product, the amount of the preparation raw materials includes: 60-100 parts by weight of a conductive polymer, 0.3-0.5 parts by weight of a second initiator, and 0.5-0.7 parts by weight of a cross-linking agent.
9. A negative electrode plate, characterized in that: The invention comprises a negative electrode active material and a binder as claimed in any one of claims 1 to 4 and / or a binder prepared by the preparation method as claimed in any one of claims 5 to 8.
10. A lithium battery, characterized in that: It comprises the negative electrode plate as claimed in claim 9, as well as a positive electrode plate, a separator and an electrolyte.